KEPEDULIAN SOSIAL DI TENGAH WABAH COVID 19 DALAM PERSEPEKTIF HADIS - Budi Suhartawan (DIRAYAH : Jurnal Ilmu Hadis, 2021)
This study explains about social care in the midst of the Covid-19 Outbreak from the Hadith Perspective. Social care is an attitude of paying attention to something that is not to interfere in other people's affairs but to help solve problems with noble goals. So that a unified social balance will be created, especially in the atmosphere of the covid-19 outbreak. The type of this research is the library research method, which is research that uses a method to obtain information data by placing existing facilities in the library, such as books, magazines, documents, historical narratives. Data on traditions related to social care were analyzed using descriptive methods. The results of this study inform that social care can be done by paying attention to each other's difficulties to increase motivation to help each other. As for the related hadith instructions regarding social care; help loosen and release the distress of others, cover the disgrace and lighten the burden of others, especially in difficult times like today. Following up on the findings in this study, the empowerment of social awareness in the midst of the Covid-19 outbreak must be further optimized through concrete actions that are more relevant to the situation of religious citizens and citizens